Microformats empowering your markup for Web 2.0 - Allsopp, John. (Apress)
Microformats burst onto the scene a couple of years ago and are fast becoming an essential tool for all professional web designers and developers. Imagine being able to integrate all of your web-based contact details, tagged articles, and geographical information seamlessly in web and desktop applications, without having to add anything extra to your websites except a little specialized HTML markup. Microformats provide a more formalized technology for adding commonly used semantics (such as contact details, location, and reviews) to today's Web. Unlike XML or the semantic Web, microformats use ubiquitous technologies like HTML and XHTML, existing developer skills, and current web tools, and, perhaps most important, they work in all of today's web browsers. This book is a comprehensive guide to microformats. It explores why—in Bill Gates' words—"We need microformats," how microformats work, and the kinds of problems microformats help solve. The book covers every current microformat, with complete details of the syntax, semantics, and uses of each, along with real-world examples and a comprehensive survey of the tools available for working with them. the book also features case studies detailing how major web content publishers such as yahoo put microformats to work in their web applications. Written by one of the Web's best-known educators, John Allsopp, Microformats: Empowering Your Markup for Web 2.0 will help you painlessly get up to speed with this exciting technology. Introducing Microformats -- What are Microformats? -- The state of the art in Microformats -- Using Microformats -- Structural and semantic HTML -- Link-based Microformats: rel-license, rel-tag, rel-nofollow, and votelinks -- Microformat to describe relationships between people: XFN -- Location Microformats: GEO and ADR -- Contact information Microformat: Hcard -- Event Microformat: Hcalendar -- Review and resume Microformats: Hreview and Hresume -- Syndicated content Microformat: Hatom -- Case studies -- Case study: Cork’d -- Case study: Yahoo -- Developing Microformats -- The process of developing Microformats.